2017
DOI: 10.1021/acsomega.7b01500
|View full text |Cite
|
Sign up to set email alerts
|

Engineered (Lys)6-Tagged Recombinant Sulfide-Reactive Hemoglobin I for Covalent Immobilization at Multiwalled Carbon Nanotubes

Abstract: The recombinant HbI was fused with a poly-Lys tag ((Lys)6-tagged rHbI) for specific-site covalent immobilization on two carbon nanotube transducer surfaces, i.e., powder and vertically aligned carbon nanotubes. The immobilization was achieved by following two steps: (1) generation of amine-reactive ester from the carboxylic acid groups of the surfaces and (2) coupling these groups with the amine groups of the Lys-tag. We analyzed the immobilization process using different conditions and techniques to different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…To show the efficient applications of the present system, electrocatalytic reduction of hydrogen peroxide and dissolved oxygen were chosen as model systems, since these reactions have been mostly performed using hemoglobin, cytochrome c, and heme-based bioelectrodes at E °′ ≈ −0.38 V versus Ag/AgCl in neutral pH solution. , It is noteworthy that compared with covalent modification, π–π bonding associated preparation of heme-chemically modified electrode showed highly efficient ETs. , For instance, Diaz-Ayala et al reported a hemoglobin covalently attached poly­(Lys-MWCNT) system has failed to show any specific redox peak for the heme at E °′ ≈ −0.380 V versus Ag/AgCl . Unlike for enzyme-based electrodes, present biomimicking system is found to be economic, quick in preparation, highly stable, and improved electrochemical performance toward the electrocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…To show the efficient applications of the present system, electrocatalytic reduction of hydrogen peroxide and dissolved oxygen were chosen as model systems, since these reactions have been mostly performed using hemoglobin, cytochrome c, and heme-based bioelectrodes at E °′ ≈ −0.38 V versus Ag/AgCl in neutral pH solution. , It is noteworthy that compared with covalent modification, π–π bonding associated preparation of heme-chemically modified electrode showed highly efficient ETs. , For instance, Diaz-Ayala et al reported a hemoglobin covalently attached poly­(Lys-MWCNT) system has failed to show any specific redox peak for the heme at E °′ ≈ −0.380 V versus Ag/AgCl . Unlike for enzyme-based electrodes, present biomimicking system is found to be economic, quick in preparation, highly stable, and improved electrochemical performance toward the electrocatalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The hemoglobin I (HbI), from the clam Lucina pectinata has a unique sequence of amino acids in the active center which are thought to be responsible for the unusually high affinity for hydrogen sulfide (H 2 S) [16,17,18,19,20]. Due to this high affinity for H 2 S, HbI has been proposed as a biocomponent for an H 2 S-biosensor [11,21] and to study H 2 S-protein interactions [19,22]. The native HbI has been cloned with an hexahistidine tag [20] and was recently fused with an hexalysine tag [23].…”
Section: Introductionmentioning
confidence: 99%
“…The polyhistidine-tag protein, (His) 6 -rHbI, has shown electrochemical activity to H 2 S after immobilization over a flat gold electrode [11]. Whereas the recombinant polylysine tag protein, (Lys) 6 -rHbI), was immobilized over carbon nanotubes via covalent conjugation [21]. These systems successfully demonstrated protein immobilization and functionality toward H 2 S, however, surface characterization and surface coverage were mostly limited by the chosen surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the higher cost and limited availability, inert metals such as gold are still preferable for biomolecule-oriented immobilization due to their stability, biocompatibility, ability for bioconjugation and enhanced physicochemical properties (e.g., optical, electronic and catalytic) [124] , [128] , [129] , [130] . Additionally, functionalized materials within a single-step such as carbon-based [8] , [60] , [131] and polymer-based matrices [60] , [65] , [67] , [133] are also successfully used in several biomedical applications ranging from regenerative therapy to smart sensors made from natural or synthetic fibers.…”
Section: Tag-mediated Purification and Immobilization Of Proteins: Recent Advances And Applicationsmentioning
confidence: 99%